Beyond the mining pit: the academic role in social deliberation for participatory environmental planning - Pena, João Carlos de Castro; Assis, Julia Camara de [UNESP]; Silva, Rafaela Aparecida da [UNESP]; Honda, Laura Kyoko [UNESP]; Pagani, Maria Inez [UNESP]; Ribeiro, Milton Cezar [UNESP] (Elsevier, 2017)
Although mining activities are required to supply human needs, the academic participation on the allocation and planning of mining activities is reduced. We presented our experience in the participatory review of Rio Claro's (São Paulo, Brazil) master plan. In 2015, Rio Claro City Hall triggered a multi-agent discussion about new perspectives on local environmental planning to improve human life quality. Representatives of economic sectors were invited for public consultations, while civil society was neglected. The academic participation was represented by amendment proposals that intended to represent common interests of society (e.g.: reducing the impacts of clay extraction on the population). We discuss the need of greater appreciation of university outreach initiatives for their high impact on public issues. Academia may ensure an equitable balance of interests between different sectors of society, aiding in the pursuit of quality of life improvement and natural resources preservation for future generations.
Keywords: Environmental planning; Master Plan; Mining impacts; Participatory process; Rio Claro